Adaptive Light Weight Encryption Algorithm for Securing Multi-Cloud Storage - et. al., Viswanath Gudditti , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In several organisations the use of cloud computing has rapidly inflated. In terms of low cost and accessibility to information, cloud computing offers several advantages. Next generation design of the IT Company was described as Cloud Computing. It moves software and expertise to centralised huge data centres where management of data and services cannot be entirely reliable. Its cost-effectiveness is the main advantage of this technology. The disadvantage is significant, however, and the security problems associated with information stored in clouds are also disadvantageous. We first identified the potential security problems and the difficulties in fully expanding cloud information and restore availability. Previous efforts have ensured the integrity of distant knowledge, but lack public verification and access to knowledge. This ensures the integrity of knowledge and ensures public verification and accessibility. We have created an elegant verification with access rights to ensure the seamless integration of these two key options in our protocol style. This paper attempts to achieve public verification by changing the traditional Merkle Hash Tree into newly materialised multi-cloud or inter-cloud. It has been shown that we can ensure the availability of knowledge with the DepSky System model for multi-clouds.